Improved Inverter Arc Welding Machine to Reduce Input Current Distorion - Panthong, Wanchai; Wattansan, Chaipat (Engineering and Applied Science Research, 2013)
Conventional inverter arc welding machines invariably employ a diode bridge to provide DC voltage for its inverter stage to transfer high-frequency power through transformer. The diode bridge draws distorted input currents which are not desirable. The paper proposes a simple and effective method to reduce the current distortion by adding two active switches to the diode bridge for current shaping. The prototype of a modified arc welding machine which can deliver a maximum welding current of 100A has been built and tested. The experimental results show that the proposed method can achieve PF of 0.98 and above while a conventional arc welding machine has PF below 0.70.